Clinical characteristics, treatment patterns, and seizure control among children with focal and generalized epilepsy at a tertiary hospital in Tanzania: A cross-sectional secondary analysis - Erneus Ernest (PLoS ONE, 2026)
This study aimed to describe the clinical characteristics and treatment patterns of children with focal and generalized epilepsy and to identify factors associated with seizure control at a tertiary hospital in Tanzania. We conducted a hospital-based cross-sectional secondary analysis of 427 children and adolescents (aged 0–17 years) with a clinical diagnosis of epilepsy whose caregivers were enrolled in a primary study between June and October 2023 at the pediatric neurology clinic of a national referral hospital in Dar es Salaam. Primary outcomes included epilepsy type distribution, treatment patterns (monotherapy vs. polytherapy and specific antiseizure medications), and level of seizure control. The secondary outcome was the identification of factors associated with seizure control, analyzed using ordinal logistic regression and reported as adjusted odds ratios (aORs). Focal epilepsy was the predominant type (52.5%). Most children (65.8%) had infantile seizure onset (<1 year) and were receiving monotherapy (74.9%). Treatment patterns were consistent with guideline recommendations: carbamazepine was prescribed to 94.6% of children with focal epilepsy, while sodium valproate was used in 96.4% of those with generalized epilepsy (both p < 0.001). Seizure freedom in the preceding month was higher among children with focal epilepsy (73.7%) compared with generalized epilepsy (59.5%, p = 0.003). In multivariable analysis, generalized epilepsy was independently associated with worse seizure control (aOR=1.93, 95% CI: 1.28–2.92, p = 0.002). Focal epilepsy was the most common type in this tertiary referral cohort, and treatment largely aligned with international guidelines. Children with generalized epilepsy were more likely to have poorer seizure control. Further prospective studies incorporating detailed syndromic and etiologic classification are needed to better define predictors of seizure control and inform service planning.